The Language of Street Children: A Sociolinguistic Study in the Regency of Klaten, Central Java - Miji Lestari, Prembayun (State Institute of Islamic Studies Salatiga, 2012)
The object of this study is the Â Street Children in the region of Klaten, particularly in the area of Klaten. The purpose of this study is to determine how Â do the language variations and the characteristics of the communities of street children related to the contemporary multicultural culture. The data is obtained from direct observation which is taken from daily conversation. The data collection is collected by tapping/recording techniques, âSimak Bebas Libat Cakapâ technique (Uninvolved Conversation Observation Technique), âSimak Libat Cakapâ (involved conversation observation Technique), taking notes and recording technique. The result is the discovery of a unique variety of language in the community of Street Children, the more usage of the Javanese particularly Ngoko Lugu level of speech containing âPisuhanâ (words of profanity) and insults.Keywords:Â Street Children Community; unique characteristics; Â âPisuhanâ (words of profanity) ; insults.Â